Regional dynamic co-management for sustainable fisheries and ecosystem conservation: a pilot analysis in the Catalan Sea - Druon, Jean-Noël; Lloret, Josep; Sala-Coromina, Joan; Recasens, Laura; Gómez, Sílvia; Bouzas, Laura Fontán; Guillen, Jordi; Tudela, Sergi (Frontiers in Marine Science, 2023)
The complexity of coastal fisheries, which often involve many gears with cross-impacts on various species and life stages, requires a management system that is able to integrate these multiple interactions in order to gradually achieve sustainability. In this paper, we argue that regional co-management can appropriately address the complex interactions between fisheries, including those with other potentially conflicting human activities. Our results, notably obtained through a questionnaire to local fishers’ representatives mainly on bottom trawl fisheries in the Catalan Sea region, show, however, that improved mutual understanding through effective communication and long-term collaboration between stakeholders, and in particular between fishers and scientists, is essential to ensure the successful implementation of fisheries co-management. In addition to balancing the voices of the many stakeholders, co-management needs to be further improved by developing multi-species, multi-gear and multi-use approaches to the oceans. This improvement could in turn support the effectiveness of co-decisions, as they would be based on the recognised administrative structure of co-management committees and sound scientific guidance that addresses both ecosystem protection and sustainable fisheries profitability. Dynamic management over time and space, using real-time essential fish habitat from operational oceanography, can help to make the co-management process more robust by improving collaboration between stakeholders and the effectiveness of measures in a changing environment. The decision-making, social and ecological components are described as integral and dependent parts of the co-management system, with priority given to mutual understanding between stakeholders. This integrated co-management framework is flexible enough to take into account regional complexity, but also national legislation and the EU Common Fisheries Policy, which all promote sustainable use of the oceans and protection of the ecosystem.